2017
DOI: 10.1088/2399-1984/aa8f91
|View full text |Cite
|
Sign up to set email alerts
|

Observation of giant conductance fluctuations in a protein

Abstract: Proteins are insulating molecular solids, yet even those containing easily reduced or oxidized centers can have single-molecule electronic conductances that are too large to account for with conventional transport theories. Here, we report the observation of remarkably high electronic conductance states in an electrochemically-inactive protein, the ~200 kD αVβ3 extracelluar domain of human integrin. Large current pulses (up to nA) were observed for long durations (many ms, corresponding to many pC of charge tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 42 publications
7
47
0
Order By: Relevance
“…Controls (buffer alone or noncognate proteins in solution) gave no signals. The rapidly fluctuating (millisecond-timescale) telegraph noise (TN) reported (15) for integrin is also observed here for anti-DNP (Fig. 1 C and D ), and all of the other proteins studied ( SI Appendix , Fig.…”
Section: Measured Conductances Depend On Contactssupporting
confidence: 76%
See 3 more Smart Citations
“…Controls (buffer alone or noncognate proteins in solution) gave no signals. The rapidly fluctuating (millisecond-timescale) telegraph noise (TN) reported (15) for integrin is also observed here for anti-DNP (Fig. 1 C and D ), and all of the other proteins studied ( SI Appendix , Fig.…”
Section: Measured Conductances Depend On Contactssupporting
confidence: 76%
“…3 E and SI Appendix , Figs. S5 and S6), implying that it is associated with fluctuations of the contacts driven by a potential drop that occurs mostly at the contacts, as previously proposed (15) and discussed in more detail below.…”
Section: Measured Conductances Depend On Contactssupporting
confidence: 70%
See 2 more Smart Citations
“…In view of the fact that important physiological processes utilize either quantum processes, for instance the photosynthetic effect in plants (Collini et al, 2010), or can be analyzed holistically similar to quantum processes (Turvey, 2015), and that proteins exhibit properties that are in a meta-stable critical quantum state (Vattay et al, 2015) it would not really be surprising to find that both the properties of single collagen molecules and the behavior of the connective tissue as a whole supports even more coherent processes than just piezoelectric ones. Indeed, it could recently be shown that certain proteins can become semiconductors and carry large electric charges, likely by a quantum process (Lindsay et al, 2017). And hemoglobin is different from chlorophyll, the molecule supporting photosynthesis, only by the fact that it contains a core of iron instead of magnesia.…”
Section: The Connective Tissue and The Interstitial Matrixmentioning
confidence: 99%